Effect of natural allergen exposure during the grass pollen season on airways inflammatory cells and asthma symptoms. Issue 6 (June 1996) - Djukanović, R; Feather, I; Gratziou, C; Walls, A; Peroni, D; Bradding, P; Judd, M; Howarth, P H; Holgate, S T
Abstract : BACKGROUND: Bronchial challenge with allergen causes a specific form of airways inflammation consisting of an influx of neutrophils, eosinophils, and T cells. Because the relevance of the challenge model to clinical asthma is uncertain, the cellular changes that occur in the lungs of asthmatic subjects during natural seasonal allergen exposure were investigated. METHODS: Seventeen grass pollen sensitive asthmatic subjects with previously reported seasonal exacerbations of asthma kept records of symptoms and underwent fibreoptic bronchoscopy with bronchoalveolar lavage (BAL) and endobronchial biopsy before and during the peak of the grass pollen season. The BAL cells were analysed for differential cell counts and by flow cytometry for T cell subsets and surface activation markers. The biopsy samples were processed into glycol methacrylate resin and immunohistochemical analysis was performed for mast cells, activated eosinophils, T cells and interleukin 4 (IL-4), a cytokine with a pivotal role in allergen-induced inflammation. RESULTS: In the pollen season there was an increase in T lymphocyte activation in the BAL fluid as identified by increased expression of interleukin 2 receptor (IL-2R). In the submucosa these changes were paralleled by an increase in CD4+ T cells. By contrast, the numbers of metachromatic cells in BAL fluid staining with toluidine blue were reduced, possibly because of degranulation following allergen stimulation. In keeping with mast cell activation, the number of mucosal mast cells staining for secreted IL-4 increased during the season. In comparison with the period shortly before the onset of the season, all but two subjects experienced an asthma exacerbation which followed the rise in pollen counts but, compared with the period preceding the first bronchoscopic examination, asthma symptoms were not increased during the pollen season. CONCLUSIONS: The data suggest that natural allergen exposure, leading to a clinical exacerbation of asthma, may induce an inflammatory response involving T cells, mast cells and eosinophils. The relationship between allergen exposure, cellular infiltration and activation, and clinical symptoms appears to be complex, with factors other than allergen also contributing to asthmatic activity.